PENGARUH METODE INQUIRY DAN DISCOVERY LEARNING SERTA TINGKAT KREATIVITAS TERHADAP KEMAMPUAN MENULIS KARANGAN DESKRIPSI PADA TARUNA NAUTIKA DAN TEKNIKA DI POLITEKNIK PELAYARAN SURABAYA - Ni Putu Dian Permata Prasetyaningrum (STKIP PGRI Jombang, 2020)
Surabaya Shipping Polytechnic emphasizes on certain areas of expertise that Taruna must possess. This is the basis after graduating from shipping polytechnics, cadets must have expertise and skills. The purpose of this study was to study the effect of inquiry, discovery learning, and creativity levels on the ability to write descriptive essays on nautical and technical cadets at Surabaya Shipping Polytechnic. This type of research is research. This research uses quantitative methods using experiments. The location used in this research is Surabaya Shipping Polytechnic. The subjects in this study were the cadets of the Nautika A, Nautika B, Teknika A, and Teknika B. classes. Based on the results of the research and discussion, the following conclusions are obtained: There are those that can be solved looking for description essays in the cadets. learning discovery method. The test results show better investigation methods than the discovery of learning, There is a difference in the ability to write a description essay about cadets who have a high level of creativity with cadets who have a low level of creativity, the test results show better who have a high level of creativity, there are related with learning methods and descriptions of the ability to write essay descriptions, the test results show learning methods and creativity descriptions of the ability to write essay descriptions.